What Is the Difference? Rereading Shakespeare’s Sonnets —An Eye Tracking Study - Xue, Shuwei; Jacobs, Arthur M.; Lüdtke, Jana (Frontiers in Psychology, 2020)
Texts are often reread in everyday life, but most studies of rereading have been based on expository texts, not on literary ones such as poems, though literary texts may be reread more often than others. To correct this bias, the present study is based on two of Shakespeare’s sonnets. Eye movements were recorded, as participants read a sonnet then read it again after a few minutes. After each reading, comprehension and appreciation were measured with the help of a questionnaire. In general, compared to the first reading, rereading improved the fluency of reading (shorter total reading times, shorter regression times, and lower fixation probability) and the depth of comprehension. Contrary to the other rereading studies using literary texts, no increase in appreciation was apparent. Moreover, results from a predictive modeling analysis showed that readers’ eye movements were determined by the same psycholinguistic features throughout the two sessions. Apparently, even in the case of poetry, the process of reading is determined mainly by surface features of the text, unaffected by repetition.